2018
DOI: 10.1080/19336934.2019.1565257
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila strain specific response to cisplatin neurotoxicity

Abstract: Drosophila melanogaster has recently been developed as a simple, in vivo, genetic model of chemotherapy-induced peripheral neuropathy. Flies treated with the chemotherapy agent cisplatin display both a neurodegenerative phenotype and cell death in rapidly dividing follicles, mimicking the cell specific responses seen in humans. Cisplatin induces climbing deficiencies and loss of fertility in a dose dependent manner. Drosophila sensitivity to cisplatin in both cell types is affected by genetic background. We sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 35 publications
1
9
0
Order By: Relevance
“…For instance, CIPN phenotypes comparable to other neuropathies have been observed in all species regardless of how the chemotherapeutic agent was administered and at which dose (Cavaletti et al, 2000;Cavaletti et al, 1995). Differences in the severity of phenotypes arose, however, these were mostly background-dependent, as shown in mice (Smith et al, 2004) and Drosophila treated with paclitaxel and cisplatin (Groen et al, 2018), respectively.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 95%
See 1 more Smart Citation
“…For instance, CIPN phenotypes comparable to other neuropathies have been observed in all species regardless of how the chemotherapeutic agent was administered and at which dose (Cavaletti et al, 2000;Cavaletti et al, 1995). Differences in the severity of phenotypes arose, however, these were mostly background-dependent, as shown in mice (Smith et al, 2004) and Drosophila treated with paclitaxel and cisplatin (Groen et al, 2018), respectively.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 95%
“…Another study tested the role of genetic background in cisplatin neurotoxicity given that humans as well as rodents respond to cisplatin in varying degrees (Groen et al, 2018). Using a negative geotactic climbing assay, the authors found a significantly different backgroundspecific response to cisplatin treatment in various wild type Drosophila strains tested.…”
Section: Cisplatin-induced Neurotoxicity In Drosophilamentioning
confidence: 99%
“…An additional manual search revealed another article in cisplatin-induced peripheral neuropathy (93). Overall, Drosophila CIPN studies focused on three common chemotherapeutics, paclitaxel (42,43,72,94), cisplatin (66,67,70,71,92), and bortezomib (69). Three of these studies (42,69,72) used Drosophila as a part of multi-model studies.…”
Section: Drosophila Models Of Cipnmentioning
confidence: 99%
“…A series of studies from the Windebank lab have pioneered Drosophila larval and adult models of cisplatin-induced peripheral neuropathy (66,67,70,71,93). The initial study in the lab used adult fly model to study the effect of cisplatin in neurons in the central nervous system and geotactic climbing behavior (93).…”
Section: Cisplatin-induced Peripheral Neuropathy Modelsmentioning
confidence: 99%
See 1 more Smart Citation